The Ins and Outs of Aurora B Inner Centromere Localization - Hindriksen, Sanne; Lens, Susanne M. A.; Hadders, Michael A. (Frontiers in Cell and Developmental Biology, 2017)
Error-free chromosome segregation is essential for the maintenance of genomic integrity during cell division. Aurora B, the enzymatic subunit of the Chromosomal Passenger Complex (CPC), plays a crucial role in this process. In early mitosis Aurora B localizes predominantly to the inner centromere, a specialized region of chromatin that lies at the crossroads between the inter-kinetochore and inter-sister chromatid axes. Two evolutionarily conserved histone kinases, Haspin and Bub1, control the positioning of the CPC at the inner centromere and this location is thought to be crucial for the CPC to function. However, recent studies sketch a subtler picture, in which not all functions of the CPC require strict confinement to the inner centromere. In this review we discuss the molecular pathways that direct Aurora B to the inner centromere and deliberate if and why this specific localization is important for Aurora B function.